Analysis of Synchronous Reluctance Motor using ANSYS Maxwell - Yildiz, Ahmet; Polat, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2023)
Energy efficiency is becoming an important issue with the increasing energy demand in the world. Electric motors play a major role in energy consumption. In this sense, it is important to increase the efficiency of electric motors. In this direction, synchronous reluctance motors with high efficiency are offered as an alternative to induction motors. Synchronous reluctance motors are the subject of research for motor designer's day by day. In this study, the design steps of the synchronous reluctance motor are summarized to enable motor designers. 1.1 kW4-pole synchronous reluctance motor is designed in ANSYS-RMxprt software. The designed model was analyzed in Finite Element Method based ANSYS Maxwell 2D software and the results were examined. © 2023 IEEE.
2023 International Conference on Power, Instrumentation, Energy and Control, PIECON 2023 -- 10 February 2023 through 12 February 2023 -- Aligarh -- 187732
Keywords: ANSYS Maxwell; Finite Element Method; motor design; synchronous reluctance motor